FENOMENA BULLYING DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM : Pendahuluan, Metode Penelitian, Hasil Penelitian dan Pembahasan, Kesimpulan - Munawir; Fitriyah, Roichatuzzuhriyah Filailatil; Khairunnisa, Salsabila Artamevia (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2024)
We often encounter the phenomenon of bullying in everyday life, whether it occurs in schools, workplaces or social environments. Not a few people in our society think that bullying only takes the form of physical violence, even though in fact bullying does not only take the form of physical violence, but also verbal violence. The Islamic religion very strictly prohibits all acts of violence, including bullying. This is found in Q.S Al-Hujurat: 11. The research method used in this research is a qualitative literature study method by examining journals/articles available online. The literature used is literature covering the last five years with the aim of studying the latest topics and developments regarding bullying. The results found in this research are the types of bullying, including physical, non-physical, relational and cyberbullying, the impact felt by victims and perpetrators which can have long or short term consequences, as well as efforts to overcome the phenomenon of bullying from a religious perspective. Islam is divided into two classifications, namely for victims and for perpetrators.